STUDYING THE TERMS OF PRODUCTION AND USE OF A COMBINED SEEDER - Nurabaev B. U.; Xamidov N. M.; Niyetullaev A. Q. (Journals Park Publishing, 2022)
In order to strengthen the ability to sow seeds of diverse dispersion and high-quality sowing, the article addresses the simplicity of the seeder system, produced when farming crops in the harsh soil and climatic circumstances of Karakalpakstan. Events with low power consumption are displayed.
Keywords: combined unit, seeder-roller, punching tool, kinematically connected ball shafts, seed spreader,